Study of the slow deformation observed at the Vyhne tidal station - DUDÁŠOVÁ, Viera (Contributions to Geophysics and Geodesy, 2021)
The results of the extensometric measurements at the Vyhne tidal station in non-tidal frequency domain are presented in the paper. Obtained results are compared with the slow deformations observed at the Sopron tidal station. We concluded, that only those strainmeters, oriented near to the N-S direction, observed real long-term strain variations of the compressional type. This phenomenon coincides with the main feature of the European recent stress field. The similarity is not yet well established in the extensometric network described in this paper due to the small number of the strainmeters and due to the possible strong and non-accurately enough known local disturbances.